War and Military Service in the Holy Scripture - Stoevsky, Grozdan (Forum Theologicum Sardicense, 2025)
What is the origin of war as a social phenomenon? What is God’s way of preventing the evil of war? What should we say about the Sixth Commandment, “Do not kill”? Should a Christian serve in the armed forces and participate in combat? This paper does not claim to provide exhaustive answers to each of these questions but aims to provoke interest and challenge the thinking of the theologically informed reader. What is the origin of war as a social phenomenon? What is God’s way of preventing the evil of war? What should we say about the Sixth Commandment, “Do not kill”? Should a Christian serve in the armed forces and participate in combat? This paper does not claim to provide exhaustive answers to each of these questions but aims to provoke interest and challenge the thinking of the theologically informed reader.